2009
DOI: 10.1017/s0016756809990446
|View full text |Cite
|
Sign up to set email alerts
|

Caledonian strike-slip terrane accretion in W. Ireland: insights from very low-grade metamorphism (illite–chlorite crystallinity and b0parameter)

Abstract: Analysis of pelites with detrital white-micas in the Clew Bay-Galway Bay segment of the Irish Caledonides indicates that b 0 data from whole-rock and < 2 μm fractions generally show differences smaller than the errors of the method, irrespective of (001) illite crystallinity values, probably due to metamorphic recrystallization. Intermediate pressure metamorphism of the Ordovician-Silurian Clew Bay Group indicates slow subduction, allowing partial thermal reequilibration before exhumation. In contrast, the Cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
(138 reference statements)
0
7
0
Order By: Relevance
“…iron contents in sphalerite- Lusk et al, 1993). However, on the basis of a gradient of ~30 to 35°C/km predicted by lattice parameter b0 data (see Padan et al, 1982, for details) from mica (Rice and Williams, 2009;Kemp and Merriman, 2009), a mean illite crystallinity value of 0.48 for pelites from the Silurian metasedimentary rocks east of the Maam Fault (Rice and Williams, 2009), which hosts the Bohaun mineralization, constrains mineralization to the late diagenetic zone of low-grade metamorphism, with a maximum mineralization depth of ~5km according to the basin maturity chart of Merriman and Frey (1999). Textures and structures described above make lithostatic fluid pressure extremely unlikely.…”
Section: Fluid Inclusion Trapping Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…iron contents in sphalerite- Lusk et al, 1993). However, on the basis of a gradient of ~30 to 35°C/km predicted by lattice parameter b0 data (see Padan et al, 1982, for details) from mica (Rice and Williams, 2009;Kemp and Merriman, 2009), a mean illite crystallinity value of 0.48 for pelites from the Silurian metasedimentary rocks east of the Maam Fault (Rice and Williams, 2009), which hosts the Bohaun mineralization, constrains mineralization to the late diagenetic zone of low-grade metamorphism, with a maximum mineralization depth of ~5km according to the basin maturity chart of Merriman and Frey (1999). Textures and structures described above make lithostatic fluid pressure extremely unlikely.…”
Section: Fluid Inclusion Trapping Temperaturesmentioning
confidence: 99%
“…The Carboniferous (Dinantian) strata form the north-western margin of the economically significant 'Irish Midlands basin', named the 'North West Province' (Phillips and Sevastopulo, 1986;Johnston et al, 1996). Outside the Dalradian, metamorphic grade in this part of Irish Caledonides is generally very low, ranging from late diagenetic zone to upper anchizone (Rice and Williams, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The horizon in the three formations where an apparently abrupt flood of detrital muscovite entered the basin was labelled the 'm-horizon'. The new field evidence and age data presented here together with the evidence presented from previous palaeontological, metamorphic and sedimentary studies (Williams, 1984(Williams, , 2002Harper et al, 1988;Evans, 1996;Harper and Parkes, 2000;Rice and Williams, 2010) require a modification of this hypothesis. The metamorphic detritus in the so-called Maumtrasna Formation can now be seen in the context of the unroofing of the Connemara Dalradian rocks to the southwest, since it is now proposed to be part of the Mweelrea Formation which contains Dalradian lithologies derived from the southwest (Pudsey, 1984;Williams, 1984).…”
Section: Plate Tectonic Modelmentioning
confidence: 60%
“…The most recent review of the Ordovician stratigraphy of the west of Ireland (Harper and Parkes, 2000) presented the Rosroe as an isolated unit and suggested that the 'south limb' was quite different to that of the 'northern limb'. A more recent study (Rice and Williams, 2010) (Figure 1). Similar to the Rosroe Formation which is along tectonic strike from the Derryveeny Formation, the latter is bound by older rocks of the Mweelrea Formation to the westnorthwest and by Silurian rocks to the south.…”
Section: Rosroe Formationmentioning
confidence: 88%
See 1 more Smart Citation